Transportation of dangerous/hazardous goods - Muhammad Khairiel Abu Bakar. (2010)
The transport of Dangerous Goods/ Hazardous Material has increased in importance with use of intermodal modes of transportation. These substances pose a threat to people, property and the environment. The International Maritime Dangerous Goods (IMDG) code and Dangerous Goods Regulations (DGR) govern transportation of such goods by sea and air respectively. Movement on roads is less specific as practices and standards vary across countries. This study investigates the current practices of transportation of such goods by various modes, with an emphasis on road transport in Singapore. It looks at the issue from the perspectives of both commercial companies involved in transport and national authorities in charge of ensuring safe movement of such goods. The study focuses on 2 broad aspects, legislation and packaging. International and national legislation have been developed over the years to characterize the properties of these substances such that the risk of an accident is reduced. This study compares the differences between legislation and analyses its significance in Dangerous Goods/Hazardous Material transport. Packaging involves the proper segregation, marking and labeling of goods for safe transport. This study compares actual practices of commercial companies and the requirements set forth in regulations. The study concludes with possible recommendations to improve the process such that essential control procedures can be enhanced to safeguard those who are potentially endangered.